Caught Between Imperial Manila and the Provincial Dynasties: Towards a New Fiscal Federalism - Mendoza, Ronald U (Archīum Ateneo, 2017)
“Imperial Manila” is often blamed for influencing public finance in at least three ways: a) by being the beneficiary of a disproportionately larger share of public spending; b) by “controlling” public spending allocations to the LGUs; and c) by passing on unfunded mandates to the LGUs. On the other hand, LGUs—notably those farthest from the capital—have become dominated by political dynasties, in turn linked to deeper poverty and underdevelopment. These two forces often contribute to a center-periphery relationship that perpetuates (or at least fails to correct) bad governance and fiscal dependence. How do we break this impasse? This paper outlines the original rationale behind decentralization and examines efforts towards more effective governance and increased fiscal independence of local government in the Philippines. It then examines some of the historical data and evidence, with a focus on provinces, cities and municipalities. It discusses some of the potential factors behind these patterns; and it concludes with possible reform options towards more effective fiscal federalism.